A Successfully Treated Multiple Metastatic Choriocarcinoma Coexistent With Live Fetus: A Case Report and Literature Review - Ding, Wei; Zhang, Na; Rao, Yang; Xu, Xiaoning; Nie, Tonggang; Qu, Pengpeng (Frontiers in Oncology, 2022)
Management of metastatic choriocarcinoma coexistent with live fetus is tricky for gynecologists. There is no consensus on treatment because of its rarity. We present a unique case of gestational choriocarcinoma with multiple metastases, who received EP chemotherapy in the third trimester. At 31+5 weeks, a healthy male baby was delivered by cesarean section. Then, she received 6 cycles of EMA/CO as postpartum chemotherapy. Her beta-human chorionic gonadotropin (β-hCG) level decreased to the normal range, and the metastases vanished. The patient had no clinical symptoms 4 years after discharge, and the baby was also free from this disease. Short tandem repeat polymorphism (STR) analysis was performed to determine the genotype of the choriocarcinoma, placenta, and normal curettage tissue of the maternal uterine. Comparing the polymorphic genetic markers revealed that the tumor was gestational choriocarcinoma, but did not originate from the coexistent pregnancy. In spite of extensive metastases, antepartum chemotherapy is an effective and safe treatment for patients with gestational choriocarcinoma concurrent with pregnancy.  STR analysis can be useful in distinguishing gestational choriocarcinoma from non-gestational, as well as the causative pregnancy, and serve as a helpful examination tool for guiding clinical management.